Judges' freedom of expression and their independence: an ambivalent relationship - Seibert-Fohr, Anja (The Rule of Law in Europe, 2021)
Whereas judges have traditionally exercised restraint in public pronouncements, there is an increasing expectation nowadays that they explain their decision-making to the broader public. On the other hand, public pronouncement of personal views may give rise to concerns about a judge’s impartiality and the authority of the judiciary more generally. Thus, divergent interests are at stake here and need to be weighed against the freedom of expression. How to balance the competing principles is the subject of this article.
Gesehen am 23.03.2022